الخطاب الإعلامي التلفزيوني في الجزائر - دراسة تحليلية للمناظرة الانتخابية ديسمبر 2019 - كحيط إيمان; قده حمزة; قدار إلهام (University Of Eloued جامعة الوادي, 2023)
هدفت الدراسة إلى التعرف على أهمية الخطاب الإعلامي في ظل الحملة الانتخابية في الجزائر ديسمبر 2019، وفي هذا السياق تناولت الدراسة مدخل مفاهيمي للخطاب الإعلامي والمناظرات التلفزيونية خلال الحملات الانتخابية، اعتمدنا في دراستنا على منهج تحليل المضمون، فيما تمثلت عينة الدراسة في الخطاب الإعلامي للمناظرة التلفزيونية للمترشحين الخمس لانتخابات ديسمبر 2019 في الجزائر باستخدام آليات التحليل المتمثلة في استخراج أسلوب الإلقاء، القوى الفاعلة ومسارات البرهنة، لتخلص الدراسة في آخرها إلى مجموعة من النتائج تمت من خلالها الإجابة على أسئلة الدراسة. The study aimed to recognize the importance of media discourse in Algeria's election campaign in December 2019. In this context, the study dealt with a conceptual introduction to media discourse and television debates during election campaigns. In our study we relied on the content analysis methodology, while the sample study was the media address of the five candidates' TV debate for the December 2019 elections in Algeria using the analysis mechanisms of extracting the delivery method. Active forces and evidentiary pathways, at the end of which the study concluded a set of results through which the study's questions were answered.
Keywords: الخطاب الإعلامي; المناظرة التلفزيونية; الحملة الانتخابية; Media discourse; TV debate; Election; Campaign